Is Together Better? Investigating the Relationship Between Network Dynamics and Congregations’ Vitality and Sustainability - McClure, Jennifer M. (2022)
BackgroundAlthough few studies have explored predictors of congregational vitality (i.e., ministry-oriented strengths, not attendance or growth) and sustainability, inter-organizational relationships matter for organizational wellbeing because of their impact on trust, cooperation, and information access. However, investigating the relationship between social capital and congregational vitality and sustainability has not previously been possible due to data limitations.PurposeThis article investigates the extent to which brokerage, or bridging together otherwise disconnected congregations, predicts congregational vitality and sustainability in an inter-congregational network of religious congregations from eight counties encompassing and surrounding a major metropolitan area in the southeastern United States. Research on social networks between organizations suggests that brokerage can have positive, negative, and curvilinear relationships with organizational outcomes, and this literature does not provide a clear expectation for how brokerage might relate with congregational vitality and sustainability.MethodsOLS regressions are used to predict three forms of vitality and two forms of sustainability using inverse network constraint, a measure of brokerage, as well as a variety of control variables. Statistical significance is estimated through permutation tests, which account for the relationships between congregations.ResultsResults indicate that brokerage is positively associated with community vitality and that staff/volunteer sustainability is highest for congregations with moderate levels of brokerage. Brokerage does not predict spiritual vitality, relational vitality, or financial sustainability.Conclusions and ImplicationsThis article has practical implications for congregations. Bridging together otherwise disconnected congregations can provide a wide range of ideas, resources, and opportunities, and these benefits can help congregations seeking to minister in their communities. In addition, moderate levels of brokerage can provide more diverse information and resources as well as a supportive, trusting, and cooperative environment. This combination of benefits may be helpful for congregations to disclose challenges with and to seek resources related to staff/volunteer sustainability. In addition, this article contributes to the fields of: congregational studies through exploring predictors of congregational vitality and sustainability; sociology of religion through expanding research using social network analysis; inter-organizational networks, whose research on social capital and organizational outcomes is both complicated and conflicting.
Keywords: Brokerage; Congregational sustainability; Congregational vitality; Network closure; Religious congregations; Social Network Analysis; Structural holes